2015
DOI: 10.1155/2015/526201
|View full text |Cite
|
Sign up to set email alerts
|

Daily Physical Activity Assessed by a Triaxial Accelerometer Is Beneficially Associated with Waist Circumference, Serum Triglycerides, and Insulin Resistance in Japanese Patients with Prediabetes or Untreated Early Type 2 Diabetes

Abstract: Aim. To investigate the association between daily physical activity and metabolic risk factors in Japanese adults with prediabetes or untreated early type 2 diabetes (T2D). Methods. Daily physical activity level was measured using a triaxial accelerometer. We assessed correlations between physical activity level and waist circumference, blood pressure, fasting levels of plasma glucose, serum triglycerides, and insulin and homeostasis model assessment-insulin resistance (HOMA-IR). Results. A total of 80 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The authors have also indicated that the results of the analysis of the physical activity level in the younger age group up to 15 years of age should be treated with the utmost caution. They also recommended the use of an objective measuring method such as an accelerometer, which is increasingly more often applied in the recent years in youth research [19,20,21,22,23,24,25].…”
Section: Methods and Research Materialsmentioning
confidence: 99%
“…The authors have also indicated that the results of the analysis of the physical activity level in the younger age group up to 15 years of age should be treated with the utmost caution. They also recommended the use of an objective measuring method such as an accelerometer, which is increasingly more often applied in the recent years in youth research [19,20,21,22,23,24,25].…”
Section: Methods and Research Materialsmentioning
confidence: 99%
“…16,17 Identifying correlates of objectively assessed physical activity and sedentary behaviour in people living with diabetes may enable us to identify certain groups of individuals with type 2 diabetes who may be more or less likely to engage in these behaviours. The aims of this study were to 1) describe the volume and patterns of daily sedentary time, as well as daily LPA and MVPA and 2) examine the socio-demographic and behavioural correlates of daily time spent sedentary, in LPA and in MVPA among adults with type 2 diabetes.…”
mentioning
confidence: 99%
“…Hence, it is important to investigate the association between daily locomotive activities such as walking and cardiovascular risk factors. Recently, we showed that daily physical activity measured by a triaxial accelerometer was favorably associated with fasting plasma glucose, blood pressure, serum triglycerides and insulin resistance in male subjects with glucose intolerance [4]. However, daily physical activity was not significantly associated with those metabolic parameters in women [4].…”
mentioning
confidence: 91%
“…Recently, we showed that daily physical activity measured by a triaxial accelerometer was favorably associated with fasting plasma glucose, blood pressure, serum triglycerides and insulin resistance in male subjects with glucose intolerance [4]. However, daily physical activity was not significantly associated with those metabolic parameters in women [4].We have certified that we comply with the Principles of Ethical Publishing in the International Journal of Cardiology. A total of 80 drug-naive patients (38 men and 42 women) with prediabetes and early type 2 diabetes were investigated.…”
mentioning
confidence: 93%
See 1 more Smart Citation